2021
DOI: 10.1177/08901171211055314
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Integrate Mobile App–Based Interventions Into Mental Health and Substance Use Disorder Treatment Services in the Wake of COVID-19

Abstract: The COVID-19 pandemic has heightened concerns about the impact of depression, anxiety, alcohol, and drug use on public health. Mobile apps to address these problems were increasingly popular even before the pandemic, and may help reach people who otherwise have limited treatment access. In this review, we describe pandemic-related substance use and mental health problems, the growing evidence for mobile app efficacy, how health systems can integrate apps into patient care, and future research directions. If eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…One possibility to reduce the cost of this and other apps could be by integrating the apps into PLWH’s health care and make them covered under this insurance program. However, health systems are still in the early stages of integrating mobile apps into care and further research is needed to understand how to best integrate apps into care and how to meet both patient and provider needs [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility to reduce the cost of this and other apps could be by integrating the apps into PLWH’s health care and make them covered under this insurance program. However, health systems are still in the early stages of integrating mobile apps into care and further research is needed to understand how to best integrate apps into care and how to meet both patient and provider needs [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian review identified 31 mobile apps and more than 100 internet sites of potential benefit for mental health [59] and reports began to appear about which mental health apps and other digital solutions were used by people with mental disorders in times of the pandemic (see, for example, Dahmen and coworkers for a study in Germany [60]). Satre and coworkers [61] described the opportunities that arose during the COVID-19 pandemic to integrate mobile app-based interventions into mental healthcare. These opportunities were influenced by increasing rates of mental disorders during the pandemic in parallel with treatment access limitations.…”
Section: The Covid-19 Pandemic: a Game Changer For Apps In Mental Hea...mentioning
confidence: 99%
“…Social sciences research has been inclining towards computer- and web-based testing for more than a decade now, emphasizing that new technologies can overcome the long-standing limitations of small and homogenous samples [ 1 , 2 , 3 , 4 ]. The outbreak of the COVID-19 pandemic only heightened the need for online tools for app-based interventions into mental health [ 5 ], primary care [ 6 ] and, importantly, online testing (e.g., the Cross-linguistic Lexical Tasks app or Naming and Inductive Reference app developed by the Multilingual Language Development and Assessment Lab (MultiLADA) at the University of Warsaw, or the Touchscreen Task for Toddlers developed at Oxford University BabyLab). This is particularly visible in developmental research since access to child participants during the pandemic was radically limited in various countries from the beginning of the pandemic [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%